High connectivity of the crocodile shark between the atlantic and southwest indian oceans: highlights for conservation - Silva Ferrette, Bruno Lopes da [UNESP]; Mendonca, Fernando Fernandes; Coelho, Rui; Vasconcelos de Oliveira, Paulo Guilherme; Vieira Hazin, Fabio Hissa; Romanov, Evgeny V.; Oliveira, Claudio [UNESP]; Santos, Miguel Neves; Foresti, Fausto [UNESP] (Public Library Science, 2015)
Among the various shark species that are captured as bycatch in commercial fishing operations, the group of pelagic sharks is still one of the least studied and known. Within those, the crocodile shark, Pseudocarcharias kamoharai, a small-sized lamnid shark, is occasionally caught by longline vessels in certain regions of the tropical oceans worldwide. However, the population dynamics of this species, as well as the impact of fishing mortality on its stocks, are still unknown, with the crocodile shark currently one of the least studied of all pelagic sharks. Given this, the present study aimed to assess the population structure of P. kamoharai in several regions of the Atlantic and Indian Oceans using genetic molecular markers. The nucleotide composition of the mitochondrial DNA control region of 255 individuals was analyzed, and 31 haplotypes were found, with an estimated diversity Hd = 0.627, and a nucleotide diversity pi = 0.00167. An analysis of molecular variance (AMOVA) revealed a fixation index phi(ST) = -0.01118, representing an absence of population structure among the sampled regions of the Atlantic Ocean, and between the Atlantic and Indian Oceans. These results show a high degree of gene flow between the studied areas, with a single genetic stock and reduced population variability. In panmictic populations, conservation efforts can be concentrated in more restricted areas, being these representative of the total biodiversity of the species. When necessary, this strategy could be applied to the genetic maintenance of P. kamoharai.